Gestão e gerenciamento de resíduos de serviços de saúde: estudo de caso no Hospital Geral Dr. César Cals de Oliveira (HGCC) - Mendonça, Cristianne Melo de (2022)
Solid Health Waste (RSS) has become a source of risk to health and the environment, mainly due to the lack of adoption of adequate technical procedures in the management of different wastes, such as contaminated biological material, sharp objects, anatomical parts, toxic, flammable substances and radioactive. The dynamics that involves the entire solid waste management process comprises a complexity of steps that has been one of the great challenges of public and private administration. Globally, solid health waste (HSW) occupies a prominent position in terms of hazardous situation, especially in the current context, the COVID-19 pandemic has exerted strong pressure on solid waste management systems in health institutions around the world. Health service establishments are responsible for the correct management of all the RSS generated by them, and it is up to public bodies, within their competence, to manage, regulate and supervise. In particular, this study has the general objective of analyzing the management of solid waste from health services (RSS) in a hospital organization of the public administration. The research was carried out using a qualitative, descriptive, exploratory approach and a single case study. As for the means, field research, bibliographic and documentary research were adopted. The collection of primary data was obtained through semi-structured interviews and application of questionnaires and the collection of secondary data was carried out through documents (PGRSS, Management Manual, current legislation). The analysis of qualitative data was carried out through content analysis. The results obtained bring a reflection on a more adequate management of solid waste and the consequences for the unit studied. The data revealed that the hospital still does not have a fully implemented management plan that can meet the needs demanded. Some factors complicate the management of this waste in misalignment with what is recommended by the legislation, being cited by the respondents: old hospital structure, lack of physical space, lack of financial resources and an educational policy with professionals who work directly in the sectors waste producers and operational. The moment of a pandemic with Covid 19 changed hospital routines, causing an overload of solid waste in the hospital, while providing changes in routines and hygiene management aimed at protecting the health of everyone in the hospital. The data found in the research reveal several possibilities for improvements for waste management, among them the focus on an educational program for all hospital employees, regardless of whether they act directly or indirectly in the production of this waste and with subsequent monitoring of the proper disposal of this waste, visualizing the reduction in production and consequently the costs resulting from improper disposal